An objective-orientated evaluation of integrated simulations on student performance in a respiratory disease course at Western Technical College and its significance to the clinical setting - Schuttenhelm, Franz T. (University of Wisconsin--Stout, 2019)
Students in healthcare education settings are hearing about and experiencing simulation-based learning material. Allowing the opportunity to use this equipment is important to incorporate in the students' learning experience. The Respiratory Therapist Program at Western Technical College has this opportunity and applying it with a more lecture-based class like Respiratory Disease is ideal. Connecting the assessment skills from the pulmonary exam and the respiratory diseases that can be concluded from those assessments, is an opportunity to be practiced with an integrated simulation mannequin. This safe practice can then be applied to the clinical setting on live patients. This study will examine the process applied from simulation to clinical in order to determine validity of the method and mannequin itself in relation to the pulmonary exam and the respiratory disease course. Decision making through assessment collection will be measured and further investigated based on student choices after a respiratory disease is diagnosed.
Keywords: Medical education; Simulation methods